Utilitarian characteristics reducing guilt: perceived values in the justification of choice. (2016) - Arruda-Filho, Emílio José Montero; Biffignandi, Silvia
Research shows that technology consumers' preferences depend on combinations of utilitarian and hedonic factors. Consumers focus on fashion, social status, differentiation from others, innovation, and bundled characteristics to feel unique. This research considers preference factors including hedonism, utilitarianism, bundle preference, social values, and technological environment, which influence consumers' behaviour and purchasing decisions. Consumers feel guilt when purchasing non-utilitarian products, and justify hedonic choices by the bundle environment and possible benefits of the integrated functionality. The article details two studies: the first defines the environmental perceptions of technology products and consumer preference, and the second analyses how consumers choose their technologies based on brand, price, and hedonic'utilitarian attributes. The study finds that hedonic and social values increase consumers' preference when characteristics increase in devices (bundle preference), while consumers justify their intention to consume related to features they already have. Social values and sense of guilt motivate consumers to justify their choices.